Using fish scales as a new biosorbent for adsorption of nickel and copper ions from wastewater and investigating the effects of electric and magnetic fields on the adsorption process. (March 2023) - Javad Sajjadi Shourije, Seyed Mohamad; Dehghan, Pouyan; Bahrololoom, Mohammad Ebrahim; Cobley, Andrew J.; Vitry, Veronique; Pourian Azar, Golnaz Taghavi; Kamyab, Hesam; Mesbah, Mohsen
Abstract: In this study, fish scales (Pomadasys kaakan's scales) were used as new biosorbent for removing Ni 2+ and Cu 2+ ions from wastewater. The effects of electric and magnetic fields on the absorption efficiency were also investigated. The effects of sorbent content, ion concentration, contact time, pH, electric field (EF), and magnetic field (MF) on absorption efficiency were assertained. In addition, the isotherm of absorption was studied in this work. This study revealed that electric field and magnetic field have significant effects on the absorption efficiency of ions from wastewater. An increase in the electric field enhanced the removal percentage of the ions and accelerated the absorption process by up to 40% in comparison with the same condition without an electric field or a magnetic field. By increasing contact time from 10 to 120 min, the removal of Ni 2+ ions was increased from 1% to 40% and for Cu 2+ ions, the removal increased from 20% to almost 95%, respectively. In addition, increasing pH, ion concentration and scales dose increased removal percentage effectively. The results indicated that using fish scales for Cu 2+ ions absorption is ideal due to the very high removal percentage (approximately 95%) without using either an electric or magnetic field. Graphical abstract: Image 1 Highlights: Fish scales were used as a new efficient biosorbent for removing Ni 2+ and Cu 2+ ions from wastewater. Approximately 95% Cu 2+  ions removal was obtained using fish scales as a biosorbent without using a magnetic or electric field. A 40% increase in the absorption process was obtained using electric and magnetic field. Magnetic and electric field have a significant effect on the absorption process of Ni 2+ ions. Biosorption is an emerging green, cost-effective and efficient alternative technology for wastewater treatment.